The Influence of Interest Rates and Inflation on Asset Allocation Strategies in Investment Portfolios in Indonesia - Cailah Nasywa Afrila; Diah Indri Anggriyanti; Maria Yovita R. Pandin (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study examines the impact of interest rates and inflation during the 2019-2023 period on asset allocation strategies in Indonesia's investment portfolio. Investment decisions are heavily influenced by two macroeconomic components, namely interest rates and inflation. These factors mainly affect how assets comprise a portfolio. In this study, data on Bank Indonesia's benchmark interest rate and the national inflation rate over the past five years are analyzed to see the pattern of change and its impact on asset allocation strategies, which include stocks, bonds, property, and other assets. The results show that rising interest rates significantly encourage people to shift from high-risk assets (e.g. stocks) to safer assets (e.g. bonds and deposits). Meanwhile, high inflation triggers an increased allocation to physical assets such as property and gold as a hedge against declining purchasing power. This research provides insights for investors to adjust their investment portfolios based on macroeconomic dynamics, especially in the face of interest rate volatility and inflation. The findings also highlight the importance of flexibility and diversification in asset allocation strategies to achieve optimal investment objectives amid economic uncertainty. The conclusion of this study confirms the importance of understanding interest rate and inflation dynamics in formulating effective investment strategies in Indonesia. The implications of these findings can be used by investors and policymakers in designing better monetary policies and investment strategies, in order to maintain national economic stability.